ANALISIS PENGARUH PENGALAMAN, INDEPENDENSI, KEAHLIAN DAN SITUASI AUDIT TERHADAP SKEPTISISME PROFESIONAL AUDITOR (STUDI PADA BPK RI PERWAKILAN PROVINSI SULAWESI UTARA DAN BPK RI PERWAKILAN PROVINSI GORONTALO) - Wowor, Pingkan Elni; Nangoi, Grace; Kalangi, Lintje (Universitas Sam Ratulangi, 2021)
The financial examiner has the duty and authority to conduct audits of the management and accountability of state finances.BPK auditors are required to have a professional attitude.The examiner's professional attitude is manifested by always being professional skepticism during the examination process. This study aims to analyze and empirically prove the effect of experience, independence, expertise and audit situation on the professional skepticism of auditors at BPK RI Representatives of North Sulawesi Province and BPK RI Representatives of Gorontalo Province. The research method used in this study is a quantitative method, using primary data through a questionnaire.Respondents in this study were examiners who worked at BPK RI Representatives of North Sulawesi Province and BPK RI Representatives of Gorontalo Province.The sample used was 84 respondents, who were directly involved in inspection activities.Data were analyzed using multiple linear regression analysis and data testing was carried out with the assistance of the SPSS version 22 program. The results showed that: 1).Experience has no significant effect on auditors' professional skepticism at BPK Representatives of North Sulawesi Province and BPK Representatives of Gorontalo Province.2).Independence has a significant effect on the professional skepticism of auditors at BPK Representatives of North Sulawesi Province and BPK Representatives of Gorontalo Province.3).Expertise does not have a significant effect on the professional skepticism of auditors at BPK Representatives of North Sulawesi Province and BPK Representatives of Gorontalo Province.4).The audit situation has a significant effect on the professional skepticism of auditors at BPK Representatives of North Sulawesi Province and BPK Representatives of Gorontalo Province.